What about the leader in Albanian reality? - Shyqyri Llaci; Mimoza Kasimati; Vasilika Kume (Journal for East European Management Studies, 2003)
It is so much written about leadership today and the leader's features are so much investigated, that one can hardly be original trying to put down some lines about the subject. Without pretending to bring new ideas, authors of this article will try here to bring new insight about leadership in a not very much studied culture like that of Albania. The following paper does take a social and organisational view of the phenomenon, trying mostly to point out the cultural influences on leadership, specific features fed by specific historical circumstances. – – Es ist schon viel über Führung geschrieben worden und die Führungseigenschaften wurden so eingehend erforscht, dass es wahrscheinlich nicht allzu originell ist, darüber zu schreiben. Ohne neue Ideen vorzugeben, versuchen die Autoren dieses Artikels, neue Einsichten von Führung in einer nicht sehr geläufigen Kultur wie der Albaniens zu geben. Der folgende Aufsatz gibt eine soziale und organisatorische Sicht der Dinge und versucht verstärkt, die kulturellen Einflüsse auf die Führung darzustellen, die von spezifischen historischen Umständen genährt wurden.
Keywords: 650; leadership; Albania; culture; history; organisation